The Need for Continuing Medical Education - Steeves, Lea C. (1965)
Continuing medical education is an essential feature of the practice of modern medicine since it furnishes the means to maintain the doctor's ability to provide quality patient care. To ensure that continuing medical education is provided efficiently and in the best quality, and utilized fully, it is necessary that: (1) the medical faculty inculcate in the student the concept of lifelong learning; (2) the practitioner adopt less time-consuming patterns of practice, to free more of his time for learning; (3) community hospital-based clinical teaching be provided universally; and (4) research be conducted to determine the best of current teaching methods and develop better ones. Conflicting efforts to meet these needs by practitioners (whose primary responsibility it is) and by organized medicine, specialty societies, voluntary health agencies and others have led to inefficient use of medical faculty teachers. The key parties in continuing medical education—practitioner and teacher—can learn best in medical school-administered programs, which need be supported by all other interested organizations.